Micro-Segregation of Ethnic Minorities in Rome: Highlighting Specificities of National Groups in Micro-Segregated Areas - Massimiliano Crisci; Michele Santurro (Land, 2023)
This paper aims to study ethnic micro-segregation in Rome, namely, high residential concentrations of ethnic groups at the micro-area level within neighbourhoods with low concentrations of these groups, with a focus on specific situations of spatial inequality often overlooked in the debate. The Italian capital is one of the five most populous cities in the European Union and a multi-ethnic metropolis with relatively low levels of segregation. It is an urban context that has been little studied, partly due to the lack of reliable and granular data. This work is based on unpublished individual data from the 2020 population register, disaggregated into 155 neighbourhoods and 13,656 census tracts with average populations of about 18,000 and 200 residents, respectively. The five minority groups considered, Bangladeshis, Chinese, Filipinos, Romanians, and migrants from developed economy countries (DECs), add up to 55% of the total foreign residents and show different settlement patterns. The concept of micro-segregated area (MSA) is central to the scope of the analysis. An MSA is a census tract that shows a strong over-representation of a specific ethnic group despite being located within a neighbourhood where that group is under-represented. MSAs can be considered ‘interstitial’ micro-areas embedded in ethnically diverse neighbourhoods. Descriptive analysis based on location quotient (LQ) mapping and bivariate logistic models is developed to highlight (a) differences in the settlement patterns of minority ethnic groups; (b) differences in the micro-segregation of minority ethnic groups in terms of socio-demographic characteristics, settlement location, and socioeconomic status; and (c) the particular characteristics of minority ethnic groups underlying these differences. The findings indicate that differences in settlement patterns can be related to the interplay between real estate constraints and labour market specialisation. National specificities in micro-segregation are mainly linked to length of stay, but the models of the Asian groups do not offer any empirical support for the spatial assimilation hypothesis, unlike those of Romanians and DECs citizens. Further development of this research will aim to explore segregation patterns and motivations to move to MSAs using a mixed method approach.